Performance of Ultrawideband Wireless Tags for On-Body Radio Channel Characterisation - Mohammad Monirujjaman Khan; Qammer H. Abbasi; Akram Alomainy; Yang Hao (International Journal of Antennas and Propagation)
Experimental characterisation of on-body radio channel for ultrawideband (UWB) wireless active tags is reported in this paper. The aim of this study is to investigate the performance of the commercially available wireless tags on the UWB on-body radio channel characterisation. Measurement campaigns are performed in the chamber and in an indoor environment. Statistical path loss parameters of nine different on-body radio channels for static and dynamic cases are shown and analyzed. Results demonstrated that lognormal distribution provides the best fits for on-body propagation channels path loss model. The path loss was modeled as a function of distance for 34 different receiver locations for propagation along the front part of the body. A reduction of 11.46% path loss exponent is noticed in case of indoor environment as compared to anechoic chamber. In addition, path loss exponent is also extracted for different body parts (trunk, arms, and legs). Second-order channel parameters as fade probability (FP), level crossing rate (LCR), and average fade duration (AFD) are also investigated.